LA INCIDENCIA DE LOS TEXTOS MEDIÁTICOS EN LA ENSEÑANZA/APRENDIZAJE DEL INGLÉS COMO LENGUA EXTRANJERA - Segovia Martín, Raquel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Apart from the book as a traditional medium for printed texts, there are other types of media, including newspapers, films, and television programs, which are also important in the transmission of texts of a different nature. On the other hand, it is also a fact that English today has become the most important language in the world of communications. Taking these considerations into account, the aim of this paper is to establish a relationship between mass media and the academic world, in order to see how the (re)productions of English language texts by several media can also provide important research and educational material for English language departments. However, the exploration of the many possibilities that media texts have in the acquisition of the English language and culture, requires an adequate development of alternative modes of text analysis as well as methodological principles on the part of researchers and instructors.